Dual VET, Germany : Chapter 19 - Le Mouillour, Isabelle [Verfasser] (My University, 2021)
This contribution describes and analyses how the in-company part of training is designed and delivered at employer level in Germany. It was written by the German expert of the European community of apprenticeship experts, which was established by the European Centre for the Development of Vocational Training (Cedefop). The European community of apprenticeship experts comprises the (then 28) EU Member States, Iceland and Norway. (BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; 370; Duales System; Betriebliche Berufsausbildung